Gustave Roussy immune score is a prognostic marker in patients with small cell lung cancer undergoing immunotherapy: a real-world retrospective study - Shangguan, Jian; Huang, Xinyi; Liu, Xu; Zhang, Zengfu; Zhang, Xiaodong; Yu, Jinming; Chen, Dawei (Frontiers in Oncology, 2023)
Background The utilization of the Gustave Roussy Immune Score (GRIm-Score) in patient selection for immunotherapy was initially reported. The objective of this retrospective study is to assess the potential of the GRIm-Score, a novel prognostic score based on nutritional and inflammatory markers, as a prognostic predictor in patients with small cell lung cancer (SCLC) undergoing immunotherapy. Methods This retrospective study conducted at a single center included 159 patients with SCLC who received immunotherapy. The objective of the study was to investigate potential differences in overall survival (OS) and progression-free survival (PFS) among patients stratified by their GRIm-Score, utilizing the Kaplan–Meier survival analysis and the log-rank test. The final independent prognostic factors were identified through both propensity score matching (PSM) analysis and multivariable Cox proportional hazards regression analysis. Results Our analysis of the 159 patients revealed that there was a significant decrease in both OS and PFS with each increase in the GRIm-Score group, displaying a stepwise pattern. Moreover, even after conducting PSM analysis, the significant associations between the modified three-category risk scale-based GRIm-Score and survival outcomes remained significant. Both the total cohort and PSM cohort were subjected to multivariable analysis, which demonstrated that the three-category risk assessment-based GRIm-Score was a valuable predictor of both OS and PFS. Conclusions In addition, the GRIm-Score may serve as a valuable and non-invasive prognostic predictor for SCLC patients undergoing PD1/PD-L1 immunotherapy.